Company Size, Leverage, and Profitability: Empirical Study on Tourism, Restaurant, and Hospitality Sub-Sector Companies - Aristi Wardani; Akhmadi Akhmadi (Indonesian Journal of Innovation Multidisipliner Research, 2025)
This study aims to analyze the effect of company size on profitability with leverage as an intervening variable in the Tourism, Restaurant and Hospitality Sub-Sector Companies for the 2014-2021 period. The technique used in collecting the sample for this research is purposive sampling technique which produces 16 companies as a sample of a population of 20 companies. The data analysis techniques using SPSS 25 to perform a t test and regression analysis of mediating variables (Causal Step).The results of this research are that the larger of company size doesn’t increase profitability. The larger of company size affect the increase in Leverage. The greater of Leverage affect the decrease in Profitability. Leverage is able to mediate the influence of Company Size on Profitability.